The Relationship Between Knowledge Of Dental And Mouth Hygiene With Ohi-S Status In Class Iv Students At Sdn Sibreh, Suka Makmur Aceh Besar District - Zahara, Elfi; Zahara, Resa; Nurdin, Nurdin; Suryani, Linda (Journal Dental Health, 2023)
Knowledge is a very important domain for the formation of an action because one's actions are influenced by the knowledge one has. Based on the results of dental examinations conducted on 10 students by researchers at SDN Sibreh, Aceh Besar, it was found that the average OHI-S status was 50% with bad criteria. This study aims to determine the relationship between dental and oral hygiene maintenance knowledge and OHI-S status in class IV students at SDN Sibreh, Suka Makmur District, Aceh Besar. This type of research is analytic method with cross sectional design. The population of this study were all 48 students of Class IV at SDN Sibreh. Sampling in this study using total sampling technique. The analysis in this study used the chi-square test. The results showed that the knowledge of maintaining dental and oral hygiene was 23 students (47.9%) in the good category and 25 students (52.1%) in the poor category. OHI-S status with good category was 10 students (20.8%), medium category was 17 students (35.4%), and bad category was 21 students (43.8%). The results of the chi-square statistical test showed that there was a relationship between knowledge of oral hygiene maintenance P value = 0.001 <0.05 and OHI-S status. Based on the results of this study it can be concluded that there is a relationship between knowledge of dental and oral hygiene maintenance and OHI-S status. It is recommended for students to further increase their knowledge, and maintain oral hygiene, na